IMPLEMENTATION OF INFORMATION SYSTEM APPLICATIONS NURSING MANAGEMENT IN - Purba, Ivan Elisabeth; Sinaga, Taruli Rohana; Adiansyah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The Hospital Nursing Management Information System is very important in supporting operations, management and decision making. The management information system in hospitals is strengthened by Regulation of the Minister of Health of the Republic of Indonesia number 82 of 2013 concerning hospital management information systems. Decision making must be based on data and information entered in a valid information system. This study aims to determine the implementation of information systems at Sari Mutiara Hospital Lubuk Pakam. This study used qualitative analysis and interviewed users of hospital information system services consisting of 1 person in charge of providing information and handling hospital complaints, 1 non-medical officer, three executors and ten information users (patients). . The results of the study show that the benefits of a data-integrated and standardized information system with Ina-CBgs coding are very much needed in decision making. The results show that it is necessary to improve the facilities and infrastructure that support a stable internet network and the implementation and monitoring of evaluation of complaints from hospital information system administrators.